Relationship between uric acid to high-density lipoprotein cholesterol ratio and sarcopenia in NHANES: exploring the mediating role of bilirubin and association with all-cause mortality - Mao, Haiyan; Zhang, Xiaoying; Huang, Shanshan; Lin, Tong; Chen, Zhikui (Frontiers in Nutrition, 2025)
BackgroundSarcopenia is a systemic disease characterized by a decline in muscle mass and function. It is associated with adverse health outcomes, and younger patients are at higher risk. Thus, early identification and prevention of high-risk factors are crucial. The uric acid to high-density lipoprotein ratio (UHR) is a novel marker of inflammation and metabolism, but studies on its association with sarcopenia are currently lacking.MethodsData from the National Health and Nutrition Examination Survey (NHANES) 2011–2018 were utilized. Weighted multivariate logistic regression analysis was performed to explore the association between UHR and sarcopenia. Causal mediation analysis was conducted to investigate the mediating role of oxidative stress factors and systemic inflammatory markers in the UHR-sarcopenia relationship. Subgroup analysis and interaction tests were performed to identify high-risk populations for the positive association between UHR and sarcopenia. Restricted cubic spline (RCS) explored potential non-linear relationships between UHR and sarcopenia. Weighted multivariate Cox proportional hazards regression analysis assessed the relationship between UHR and all-cause mortality in sarcopenia patients.ResultsA total of 10,308 adult participants aged ≥ 20 years were included in the study, with 901 diagnosed with sarcopenia. The weighted multivariate logistic regression analysis showed a significant positive association between UHR and sarcopenia after adjusting for all confounding factors (OR = 1.057; 95% CI: 1.037–1.077; P < 0.001). Total bilirubin mediated −8.53% of the association between UHR and sarcopenia (95% CI: −13.42% to −5.91%; P < 0.001). The subgroup analysis and interaction test results indicate that the positive association between the two variables is relatively stable across different populations. RCS analysis revealed no significant non-linear relationship between UHR and sarcopenia (P = 0.167). Weighted multivariate Cox proportional hazards regression analysis showed a significant positive association between UHR and all-cause mortality in sarcopenia patients (HR = 1.053; 95% CI: 1.024–1.083; P < 0.001) in the unadjusted model. However, after adjusting for all covariates, UHR maintained a positive association with all-cause mortality in sarcopenia patients (HR = 1.023; 95% CI: 0.990–1.056), though this association did not reach statistical significance (P = 0.173).ConclusionElevated UHR shows a significant association with sarcopenia prevalence and exhibits a positive association trend with all-cause mortality among affected individuals. These findings suggest that UHR may serve as a potential indicator for sarcopenia risk assessment. Further prospective studies are warranted to validate its clinical utility for early screening and intervention strategies.